Increased Hemoglobin Oxygen Affinity With 5-Hydroxymethylfurfural Supports Cardiac Function During Severe Hypoxia - Lucas, Alfredo; Ao-ieong, Eilleen S. Y.; Williams, Alexander T.; Jani, Vivek P.; Muller, Cynthia R.; Yalcin, Ozlem; Cabrales, Pedro (Frontiers in Physiology, 2019)
Acclimatization to hypoxia or high altitude involves physiological adaptation processes, to influence oxygen (O2) transport and utilization. Several natural products, including aromatic aldehydes and isothiocyanates stabilize the R-state of hemoglobin (Hb), increasing Hb O2 affinity and Hb O2 saturation. These products are a counter intuitive therapeutic strategy to increase O2 delivery during hypoxia. 5-Hydroxymethylfurfural (5-HMF) is well known Amadori compound formed during the Maillard reaction (the non-enzymatic browning and caramelization of carbohydrate-containing foods after thermal treatment), with well documented effects in Hb O2 affinity. This study explores the therapeutic potential of 5-HMF on left ventricular (LV) cardiac function (LVCF) during hypoxia. Anesthetized Golden Syrian hamsters received 5-HMF i.v. at 100mg/kg and were subjected to stepwise increased hypoxia (15%, 10%, and 5%) every 30 minutes. LVCF was assessed using a closed chest method with a miniaturized conductance catheter via continuous LV pressure-volume (PV) measurements. Heart hypoxic areas were studied using pimonidazole staining. 5-HMF improved cardiac indices, including stroke volume (SV), cardiac output (CO), ejection fraction (EF), and stroke work (SW) compared to the vehicle group. At 5% O2, SV, CO, EF, and SW were increased by 53%, 42%, 33%, and 51% with 5-HMF relative to vehicle. Heart chronotropic activity was not statistically changed, suggesting that differences in LV-CF during hypoxia by 5-HMF were driven by volume dependent effects. Analysis of coronary blood flow and cardiac muscle metabolism suggest no direct pharmacological effects from 5-HMF, therefore these results can be attributed to 5-HMF dependent increase in Hb O2 affinity.